2021
DOI: 10.2147/ceor.s301169
|View full text |Cite
|
Sign up to set email alerts
|

Change and Innovation in Healthcare: Findings from Literature

Abstract: Background:Change is an ongoing process in any organizations. Over years, healthcare organizations have been exposed to multiple external stimuli to change (eg, ageing population, increasing incidence of chronic diseases, ongoing Sars-Cov-2 pandemic) that pointed out the need to convert the current healthcare organizational model. Nowadays, the topic is extremely relevant, rendering organizational change an urgency. The work is structured on a double level of analysis. In the beginning, the paper collects the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 90 publications
0
23
0
4
Order By: Relevance
“…A high level of readiness for change is crucial to the implementation of any organisational change, 56 including in the medical sphere, 57 , 58 and medical laboratories are no exception. The starting point of QMS implementation and laboratory quality improvement should be sufficient preparation for the implementation initiative.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A high level of readiness for change is crucial to the implementation of any organisational change, 56 including in the medical sphere, 57 , 58 and medical laboratories are no exception. The starting point of QMS implementation and laboratory quality improvement should be sufficient preparation for the implementation initiative.…”
Section: Resultsmentioning
confidence: 99%
“… 26 , 28 , 30 , 31 , 37 , 41 , 42 , 44 , 45 , 47 , 48 , 49 , 53 Our results correspond to the findings of other studies that have recognised the psychological aspect of organisational changes and individual change acceptance as key components of success in healthcare innovation. 57 , 58 …”
Section: Resultsmentioning
confidence: 99%
“…Consequently, when this change is actively introduced, it may produce negative feelings among the CHWs, ranging from resentment, low motivation, preference for stability, to insecurity, ultimately leading to inadequate levels of engagement with the change intervention (Armenakis et al, 1993;Jones et al, 2008). Previous research has shown higher individual-level readiness for change to be associated with higher levels of initiative and cooperation that ultimately supports the successful implementation of change (George & Jones, 2001;Milella et al, 2021). Moreover, studies have found that knowledge-and skills-based training alone was insufficient in improving CHWs' performance in implementing health care services (Charlson et al, 2019;Heller et al, 2019;Rowe et al, 2018).…”
Section: Task Sharing and Readiness For Changementioning
confidence: 99%
“…All these tendencies have highlighted an indisputable truth: to properly solve all these issues and to ensure coordination, connectivity, continuity and accountability, radical changes are needed in the health care system. If we carefully examine the above factors, it is clear that each of them is, in essence, driven by the need to improve the quality, limit the costs of health care, and improve the access of individuals in need to the health care system [1], [2]. All these factors increase the need for information for all actors involved, such as health-care staff at every level of the health-care system (tertiary, secondary, and primary), as well as for managers of health organizations and the health system in general, societies of health insurance, but also for patients or users of the health-care system.…”
Section: Introductionmentioning
confidence: 99%
“…All these factors increase the need for information for all actors involved, such as health-care staff at every level of the health-care system (tertiary, secondary, and primary), as well as for managers of health organizations and the health system in general, societies of health insurance, but also for patients or users of the health-care system. This is because, to improve the quality of health care, to identify interventions or cost-effective measures and to make decisions of a strategic nature, it is necessary to have available data related to clinical activity and results, as well as related to procedures and administrative aspects of health care; the need for such data is only increasing due to the increasing pressure on the health system to provide high-quality health care at a reasonable cost [1], [2].…”
Section: Introductionmentioning
confidence: 99%